2022
DOI: 10.1111/dom.14804
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curcumin on hepatic fat content in individuals with obesity

Abstract: Aim: To evaluate the effect of curcumin treatment on hepatic fat content in obese individuals.Materials and Methods: In a double-blind, parallel-group trial, 37 obese, non-diabetic individuals were randomized to placebo or curcumin treatment for 6 weeks. Curcumin was dosed as lecithin-formulated tablet; 200 mg twice daily. The primary endpoint was hepatic fat content as assessed by magnetic resonance spectroscopy (MRS). Other endpoints included anthropometric measurements, hepatic biomarkers including FibroSca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The effect of curcumin on circulating glucagon concentrations is uncertain and the present results indicate that curcumin does not affect prednisolone-induced hyperglucagonaemia in humans. A previous study by our group in obese individuals showed no effects of curcumin on circulating glucagon concentrations after 6 weeks treatment ( 45 ).…”
Section: Discussionmentioning
confidence: 74%
“…The effect of curcumin on circulating glucagon concentrations is uncertain and the present results indicate that curcumin does not affect prednisolone-induced hyperglucagonaemia in humans. A previous study by our group in obese individuals showed no effects of curcumin on circulating glucagon concentrations after 6 weeks treatment ( 45 ).…”
Section: Discussionmentioning
confidence: 74%
“…In humans, reports of the effect of curcumin on anthropometric parameters have been carried out in trials with patients with overweight or obesity combined with other pathologies. Although many studies have reported that curcumin reduces waist circumference [ 181 , 182 ] in patients with grade III obesity, no significant decrease in this variable or visceral fat was found [ 183 ]. In some clinical trials and meta-analyses, no significant reductions in BMI and weight have been found [ 181 ]; however, when performing the statistical analysis by groups, a decrease was found [ 182 ].…”
Section: Molecules With Demonstrated Clinical Efficacy In the Prevent...mentioning
confidence: 99%
“…The trials listed on clinicaltrials.gov report the use of capsules or tablets of curcumin alone or of phospholipids and curcumin together (see Table 4 ). In particular, trials evaluating the efficacy and safety of curcumin in both NAFLD and obese patients at different doses [ 280 , 281 ] assessed both the reduction in fibrosis by the use of Fibroscan [ 280 ] and serum levels of inflammatory markers or fat/glucose parameters [ 281 ], but these results were not significantly different from those observed in the placebo group.…”
Section: Possible Therapeutic Approachesmentioning
confidence: 99%